A new species of the genus Pseudocosmetura Liu, Zhou & Bi, 2010 (Orthoptera: Tettigoniidae: Meconematinae) from Sichuan Wanglang National Nature Reserve, China - Shi, Fuming; Zhao, Lianjun (Zootaxa, 2018)
The paper described one new species from Sichuan, China. The new species, i.e. Pseudocosmetura wanglangensis sp. nov. differs from the known species of the genus in its distinctive male cercus and epiproct.